2008
DOI: 10.1037/0022-006x.76.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors associated with trajectories of depressed mood from adolescence to early adulthood.

Abstract: This study used semi-parametric group-based modeling to explore unconditional and conditional trajectories of self-reported depressed mood from age 12 to 25. Drawing on data from the National Longitudinal Study of Adolescent Health (N=11,559), four distinct trajectories were identified: no depressed mood, stable low depressed mood, early high declining depressed mood, and late escalating depressed mood. Baseline risk factors associated with greater likelihood of membership in depressed mood trajectory groups c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
322
6
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(388 citation statements)
references
References 91 publications
54
322
6
6
Order By: Relevance
“…Previous findings of social connectedness being negatively correlated with loneliness and depression concurrently have also been reported by several authors (e.g., Libbey et al, 2002). Longitudinal studies examining the link between multiple aspects of connectedness and adolescents wellbeing are still lacking, but existing literature (Costello et al, 2008;Hall-Lande et al, 2007;Jose et al, 2012;McGraw et al, 2008;Olsson et al, 2013) has identified a positive impact of social connectedness on adolescent's loneliness and depression. In the present study, we found, in line with the findings from other longitudinal studies, significant longitudinal correlations between social connectedness, loneliness and depression in the expected directions.…”
Section: Overview Of Findings Within the Context Of The Literaturementioning
confidence: 62%
See 1 more Smart Citation
“…Previous findings of social connectedness being negatively correlated with loneliness and depression concurrently have also been reported by several authors (e.g., Libbey et al, 2002). Longitudinal studies examining the link between multiple aspects of connectedness and adolescents wellbeing are still lacking, but existing literature (Costello et al, 2008;Hall-Lande et al, 2007;Jose et al, 2012;McGraw et al, 2008;Olsson et al, 2013) has identified a positive impact of social connectedness on adolescent's loneliness and depression. In the present study, we found, in line with the findings from other longitudinal studies, significant longitudinal correlations between social connectedness, loneliness and depression in the expected directions.…”
Section: Overview Of Findings Within the Context Of The Literaturementioning
confidence: 62%
“…When individual domains of connectedness were examined, bi-directional relationships between connectedness and wellbeing emerged, particularly for family and school connectedness, suggesting that adolescents had a qualitatively different experience when engaging with schools compared with engaging with peer groups. Drawing their data from the National Longitudinal Study of Adolescent Health, Costello, Swendsen, Rose, and Dierker (2008) found that adolescents who reported greater feelings of connection to parents, peers, and school were more likely to be classified in the no-depressed mood group than either the stable low or early high declining depressed group. The 15-wave (32-year) Dunedin Multidisciplinary Health and Development Study found that adolescents' reports of social connectedness predicted well-being over a decade later, and lack of family connectedness manifested a strong, inverse link with social connectedness in childhood that continued into adolescence, highlighting the enduring significance of positive interpersonal relationship (Olsson, McGee, Nada-Raja, & Williams, 2013).…”
Section: Social Connectedness As a Protective Factormentioning
confidence: 99%
“…For example, previous studies showed that optimism (e.g., Piko et al, 2009), family coherence (e.g., Costello et al, 2008), self-awareness (e.g., Tandon & Solomon, 2009), and emotion regulation (e.g., Van Vorhees et al, 2008) are associated with a lower likelihood of developing depressive symptoms. Similarly, research generally supports the protective influence of peer support (e.g., Babiss & Gangwisch, 2009) and self-efficacy (Beautrais, 2003) on suicidal thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, assets that protect against depression include individual, peer, family, school, and community factors. These assets include everything from optimism (e.g., Piko, Kovacs, & Fitzpatrick, 2009) to connectedness to family, peers, and school (e.g., Costello, Swednsen, Rose, & Dierker, 2008) to community engagement (e.g., Van Vorhees et al, 2008). Although identifying all of the assets that might protect youth from negative developmental outcomes is of interest, it is simply not feasible to assess for and intervene with all of these factors.…”
Section: Factors Protecting Adolescents From Risk Behaviors and Emotimentioning
confidence: 99%
“…[4][5][6] Several factors have been associated with the development of depressive symptoms in adolescents. Female sex and age have been found to be particularly important, 5 and some studies showed that alcohol and tobacco use are risk factors for depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%